2021
DOI: 10.23887/jet.v5i1.33629
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Managerial Ability of School Principals and The Climate of School Organizations on Teacher Performance During The Covid-19 Pandemic

Abstract: The role of school principals is very important in optimizing teacher performance during the Covid-19 pandemic. In addition, a conducive school organizational climate is able to provide solutions to teacher performance problems that arise during the Covid-19 pandemic. This study aims to analyze the effect of Principal Managerial Ability and School Organizational Climate on Teacher Performance During the Covid-19 Pandemic. This type of research is quantitative research. The research method used is a quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Four dimensions of school organizational climate are relationship, personal growth, system change and improvement, and physical environment have been constantly researched on (Khuluqo & Tenkahary, 2021). These four dimensions adopted through climate studies identified as institutional vulnerability, professional teacher, collegial leadership and achievement press (Hoy et al, 2002) are also used in constructing the Organizational Climate Index (OCI) (Hoy et al, 1998).…”
Section: Influential Factors In School Organizational Climatementioning
confidence: 99%
“…Four dimensions of school organizational climate are relationship, personal growth, system change and improvement, and physical environment have been constantly researched on (Khuluqo & Tenkahary, 2021). These four dimensions adopted through climate studies identified as institutional vulnerability, professional teacher, collegial leadership and achievement press (Hoy et al, 2002) are also used in constructing the Organizational Climate Index (OCI) (Hoy et al, 1998).…”
Section: Influential Factors In School Organizational Climatementioning
confidence: 99%